A convenient synthesis of 2-acyl benzothiazoles/thiazoles from benzothiazole/thiazole and N, N'-carbonyldiimidazole activated carboxylic acids. Issue 25 (20th June 2019) - Huang, Tonghui; Wu, Xin; Yu, Yongbo; An, Lin; Yin, Xiaoxing
Graphical abstract: Conditions: (a) i -PrMgCl·LiCl, THF, −10 °C, 30 min. (b) N, N'-carbonyldiimidazole, THF, r.t., 1 h. (c) THF, −10 °C to r.t., 3 h. Highlights: Synthesis of 2-acyl benzothiazoles/thiazoles from various carboxylic acids. Appropriate for Boc-protected amino acids and dipeptide. Moderate to excellent yields under mild reaction conditions. Abstract: A convenient and efficient strategy for the synthesis of 2-acyl benzothiazoles/thiazoles has been developed. The treatment of benzothiazole/thiazole with allylic Grignard reagents readily generates the corresponding 2-Grignard reagents, which is followed by a reaction with N, N'-carbonyldiimidazole activated carboxylic acids to afford various 2-acyl benzothiazoles/thiazoles products. The synthetic method is applicable to a wide array of carboxylic acids and allows easy access to 2-acyl benzothiazoles/thiazoles with considerable yields under mild reaction conditions.